Genetic analysis of grain yield and resistance of extra-early-maturing maize inbreds to northern corn leaf blight - Badu-Apraku, Baffour; Bankole, F.; Fakorede, M.A.B.; Ayinde, O.; Ortega Beltran, A. (Wiley, 2021)
Maize (Zea mays L.) is a food security crop in sub-Saharan Africa (SSA). Incidence of northern corn leaf blight (NCLB), caused by Exserohilum turcicum, in lowlands of SSA during the past decade has caused 30–70% reduction in maize yield. This study (a) examined the combining abilities of extra-early maize (EEM) inbreds and classified them into heterotic groups; (b) elucidated gene action controlling resistance to NCLB; (c) assessed grain yield (GYLD) and yield stability of EEM hybrids underNCLB infection; and (d) identified testers. One hundred and fiftyEEMhybrids, obtained by crossing 15 inbreds each of white- and yellow-endosperm maize using the North Carolina Design II, plus six checks, were evaluated in nine environments, six of which were inoculated with an isolate of E. turcicum and three of which were non-inoculated in 2018 and 2019. The white and yellow inbreds were placed in three heterotic groups using the heterotic grouping based on general combining ability (GCA) of multiple traits and stability of GYLD using the genotype plus genotype × environment (GGE) biplot analysis. The GCA, specific combining ability (SCA) and genotype × environment (G×E) interactions were significant for GYLD, disease severity, and other measured traits. The GCA effects were more important than the SCA effects for GYLD and NCLB severity scores across environments, implying that recurrent selection could facilitate improvement for GYLD and NCLB resistance. Three inbred testers and four single-cross testers were identified for developing high-yielding NCLB-resistant hybrids. Four white and five yellow single-cross hybrids were identified for on-farm testing and possible commercialization.